The mouse and the rat in surgical research. The anesthetic approach - CHANIOTAKIS, I.; SPYRLIADIS, A.; KATSIMPOULAS, M.; KOSTOMITSOPOULOS, N. (Journal of the Hellenic Veterinary Medical Society, 2018)
The mouse and the rat are currently overwhelmingly preferred as laboratory animals. Surgical research on animals requires anesthesia and analgesia to obtain adequate immobility and to reduce stress and pain. Small rodent anesthesia is challenging for several reasons including the animals’ size, metabolic rate, high risk of hypothermia and difficulty in monitoring. The purpose of this study is to create an overview of the information in the anesthetic practices for small rodents, in particular mice and rats.